2006
DOI: 10.1289/ehp.8459
|View full text |Cite
|
Sign up to set email alerts
|

Intersubject Variability of Risk from Perchlorate in Community Water Supplies

Abstract: This article is a brief review and summary of the estimated incremental risks (increases in hazard quotient or decreases in thyroid uptake of iodine) to pregnant women (and hence their fetuses) associated with perchlorate exposure in community water supplies (CWSs). The analysis draws on the recent health effects review published in 2005 by the National Research Council (NRC). We focus on the potential level of risk borne by the NRC-identified most sensitive subpopulation (pregnant women and hence their fetuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…RfDs are traditionally based on the no‐observed‐adverse‐effect level (NOAEL) and not the NOEL. By definition a NOAEL is an adverse effect equal to or higher than a NOEL when the effect used to establish the NOEL is a precursor to the adverse effect of interest in establishing a NOAEL (Crawford‐Brown et al, 2006). Even though the NOEL is considered a more conservative threshold for establishing an RfD, this approach has been criticized in the case of perchlorate as not being sufficiently protective of human health (Ginsberg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…RfDs are traditionally based on the no‐observed‐adverse‐effect level (NOAEL) and not the NOEL. By definition a NOAEL is an adverse effect equal to or higher than a NOEL when the effect used to establish the NOEL is a precursor to the adverse effect of interest in establishing a NOAEL (Crawford‐Brown et al, 2006). Even though the NOEL is considered a more conservative threshold for establishing an RfD, this approach has been criticized in the case of perchlorate as not being sufficiently protective of human health (Ginsberg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These questions address a household’s ability to meet essential expenses such as rent, utility, and medical bills; the ability to see a doctor or dentist as needed; and the adequacy of food availability. Based on the Bauman (1998) SIPP analysis, and similar hardship or financial distress studies, a hierarchy of household necessities can be constructed as shown in Figure 1 (Crawford-Brown et al., 2009).…”
Section: Health–health Analysis and Standard Settingmentioning
confidence: 99%
“…Perchlorate was detected in natural waters (rain water), raw and treated drinking water, groundwater, bottled water, open well and surface water in the United States, India, England, and Wales, China, South Korea, Japan, and Canada (Srinivasan and Viraraghavan, 2009;Tikkanen, 2006;Stetson et al, 2006;Kannan et al, 2009;McLaughlin et al, 2011;Anupama et al, 2012, Snyder et al, 2005Crawford-Brown et al, 2006;Rajagopalan et al, 2006;Stetson et al, 2006;Kimbrough and Parekh, 2007;Kosaka et al, 2007;Quinones et al, 2007;Wagner et al, 2007). In the United States, perchlorate detection in 26 states, including Puerto Rico, Mariana Islands, and in the public water systems resulted in the discontinuation of the use of most of the perchlorate-contaminated sources (Brandhuber et al, 2009).…”
Section: Fate and Transportmentioning
confidence: 99%